The Effect of Government Expenditure on the Level of Poverty in the People's Republic of North Sumatra Province in 2010-2021 - Akase Sitinjak (PT FORMOSA CENDEKIA GLOBAL, 2022)
Poverty has become a common problem to hear about, but it is also a problem point that has not been resolved until today's progress. The purpose of this study is to find out how the influence of government spending on poverty levels in the province of North Sumatra. The data used for this research is secondary data. The data collection technique is through observation from North Sumatra bps data https://sumut.bps.go.id/. The research technique used in this research is path analysis. The results of the research using SPSS 25 data show that North Sumatra provincial government spending from 2010-2021 has a significant but negative effect on the poverty level of the people of North Sumatra province.